Method and device for characterizing time-varying characteristics of mechanical properties of composite material in curing process

By using composite material repair instruments and self-consistent field mesoscopic mechanical model, combined with differential scanning calorimetry and mechanical testing machine, the difficulty in measuring the time-varying characteristics of mechanical properties during the curing process of composite materials is solved, and accurate mechanical properties characterization and manufacturing accuracy are achieved.

CN119860977AActive Publication Date: 2025-04-22AVIC XIAN AIRCRAFT IND GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411897694.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-22
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

It is difficult to accurately characterize the time-varying characteristics of the composite material during curing, resulting in difficulty in analyzing and solving residual stresses and curing deformations.

Method used

The composite material repair instrument is used to combine differential scanning calorimetry and mechanical testing machine to inversely deduce the time-varying characteristics of the composite material under different curing degrees through the self-consistent field mesoporosis mechanical model.

Benefits of technology

It realizes accurate measurement of the time-varying characteristics of the mechanical properties of composite materials, reduces errors, improves manufacturing accuracy, and can effectively analyze and solve manufacturing defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119860977A_ABST
    Figure CN119860977A_ABST
Patent Text Reader

Abstract

The invention provides a characterization method and a characterization device for time-varying characteristics of mechanical properties of a composite material in a curing process. The characterization method comprises the following steps: step 1, obtaining reaction enthalpy released by complete curing of a to-be-detected prepreg with unit mass; 2, obtaining multiple groups of compression samples and DSC samples; 3, curing the compression sample and the DSC sample at the same time by adopting a composite material repairing instrument, terminating the curing process of each group of samples at different preset time, and recording the temperature T of each group of samples at the curing termination; step 4, for each group of samples, measuring the compression modulus of the compressed sample at the corresponding temperature T after the step 3 by using a mechanical testing machine, and obtaining the curing degree of the DSC sample after the step 3; 5, according to the multiple sets of curing degrees and compression moduli, the moduli of the resin under the different curing degrees are obtained through backstepping by means of the self-consistent field mesomechanics model, and then the time-varying characteristics of the mechanical property of the composite material in the curing process can be obtained. The characteristics that the composite material repairing instrument can safely and controllably terminate the composite material curing process at any time, the mechanical property of the composite material in the thickness direction, the compression test is easy to implement and the like are fully combined, and the problems that composite material mechanical samples are difficult to machine and mechanical properties are difficult to measure under different curing degrees and different temperatures are solved; accurate measurement of the time-varying characteristic of the mechanical property of the composite material is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite material mechanical property characterization, in particular to a method and a device for characterizing the time-varying characteristics of mechanical properties during a composite material curing process. Background Art

[0002] During the curing process, thermosetting resin-based composite materials will undergo a transition from viscous flow state to rubber state and glass state, and their mechanical properties will change with the curing process. The time-varying characteristics of the mechanical properties of composite materials are one of the main reasons for the generation of residual stress and component curing deformation. Therefore, the accurate characterization of the corresponding relationship between the mechanical properties of composite materials and the degree of curing is the basis for the precise manufacturing of composite materials.

[0003] The degree of cure of composite materials is usually measured by DSC (differential scanning calorimeter), and the measurement of the time-varying characteristics of its mechanical properties generally includes empirical methods and DMA (dynamic thermomechanical analysis) measurement methods. On the one hand, the empirical method is based on the mechanical properties of uncured and fully cured composite materials, combined with empirical formulas and self-consistent field micromechanical models to infer the mechanical properties of uncured composite materials, and is obtained by fitting relevant time-varying models, such as the method used in the Chinese patent with publication number CN 110197008B and publication date December 25, 2020. However, there is a certain error between the results calculated based on the empirical formula and the actual situation. On the other hand, since the DMA test cannot provide accurate modulus values, the DMA measurement method obtains the change of the modulus of the composite material with the curing process through the DMA test, and at the same time, the self-consistent field micromechanical model is used to infer the time-varying characteristics of the mechanical properties of the composite material. This method will introduce certain errors when inferring the resin properties in the low modulus region.

[0004] The difficulty in characterizing the time-varying characteristics of mechanical properties of prepreg during the curing process is that it is difficult to prepare mechanical test specimens with different curing degrees due to the limitations of autoclave equipment. Therefore, a method for characterizing the time-varying characteristics of mechanical properties of thermosetting composite materials is proposed, which has important engineering significance for the analysis and resolution of typical manufacturing defects of composite materials. Summary of the invention

[0005] The mechanical properties of composite materials evolve with the curing process. In order to accurately characterize the changing laws of the mechanical properties of composite materials under different curing degrees, the present invention provides a method and device for characterizing the time-varying characteristics of the mechanical properties of composite materials during the curing process. The composite material repair instrument is used to solve the problem of difficult preparation of mechanical specimens with different curing degrees. The differential scanning calorimetry and mechanical testing machine are combined, and the direct measurement of the time-varying characteristics of the mechanical properties of composite materials is realized based on the self-consistent model, which ensures the accuracy of the results.

[0006] The first aspect of the present invention provides a method for characterizing the time-varying characteristics of mechanical properties during the curing process of a composite material, comprising:

[0007] Step 1: Obtain the reaction enthalpy released by the complete curing of the prepreg to be tested per unit mass;

[0008] Step 2: Obtain multiple sets of compression specimens and DSC specimens;

[0009] Step 3: Use a composite material repair instrument to cure the compression specimen and the DSC specimen at the same time, terminate the curing process for each group of specimens at a different preset time, and record the temperature T of each group of specimens at the end of curing;

[0010] Step 4: For each group of samples, the compression modulus of the compressed sample after step 3 at the corresponding temperature T is measured using a mechanical testing machine to obtain the degree of curing of the DSC sample after step 3;

[0011] Step 5: Based on multiple groups of curing degrees and compression moduli, the self-consistent field micromechanics model is used to inversely infer the modulus of the resin at different curing degrees, and then the time-varying characteristics of the mechanical properties of the composite material during the curing process can be obtained.

[0012] Optionally, obtaining the reaction enthalpy H released by fully curing the prepreg to be tested per unit mass includes:

[0013] The reaction enthalpy H released by the complete curing of the prepreg per unit mass is tested and calculated according to ASTM E2160.

[0014] Optionally, obtaining the degree of curing of the DSC sample after step 3 includes:

[0015] The DSC sample is subjected to dynamic DSC scanning to obtain the residual reaction enthalpy ΔH per unit mass of the sample, and the curing degree α of the DSC sample is calculated according to α=(1-ΔH) / H.

[0016] Optionally, obtain a compression specimen, including:

[0017] According to symmetry [0 / 90] ns The prepreg is laid in a ply order to form a prepreg blank, and after sufficient cold drawing and compaction, the edge of the prepreg blank is trimmed to obtain a compression specimen;

[0018] The size of the compression specimen is 50mm*50mm, and the ply information is [0 / 90] ns Where n is a positive integer not less than 5.

[0019] Optionally, obtain a DSC sample, including:

[0020] 5 to 25 mg of the prepreg to be tested was placed in an aluminum crucible to prepare a DSC sample.

[0021] Optionally, the mechanical testing machine is equipped with a temperature control box, and when the compression modulus is measured using the mechanical testing machine, the temperature of the temperature control box is controlled to be T.

[0022] Optionally, using a mechanical testing machine to measure the compression modulus of the compression sample after step 3 at a corresponding temperature T, including:

[0023] A compression test is performed on the compression specimen to obtain a force-displacement curve, and a set of force F and compression displacement l0 is obtained from the linear segment of the initial compression stage in the force-displacement curve;

[0024] According to the force F and the compression displacement l0; using the formula Obtain the compression modulus E;

[0025] Among them, S represents the effective compression area and l represents the original thickness of the sample.

[0026] Optionally, obtain multiple sets of compression specimens and DSC specimens, including:

[0027] Obtain no less than 5 sets of compression specimens and DSC specimens.

[0028] Optionally, after obtaining the degree of curing of the DSC sample after step 3, the method further comprises:

[0029] Determine whether the number of samples with a degree of cure exceeding a preset gel point is less than 3;

[0030] If yes, add a new sample group and a different preset time.

[0031] A second aspect of the present invention provides a device for characterizing the time-varying characteristics of mechanical properties during the curing process of a composite material, which is used to execute the method as described in any one of the first aspects.

[0032] The present invention provides a method and device for characterizing the time-varying characteristics of mechanical properties in the curing process of a composite material. The method and device fully combine the characteristics that a composite material repair instrument can safely and controllably terminate the curing process of a composite material at any time, the mechanical properties in the thickness direction of the composite material, and the easy implementation of a compression test, thereby solving the problems of difficult processing of mechanical specimens of composite materials at different curing degrees and temperatures and difficult measurement of mechanical properties, and realizing accurate measurement of the time-varying characteristics of the mechanical properties of composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is the dynamic DSC scanning curve of the prepreg system measured in Example 2 of the present invention;

[0034] Figure 2 The experimental measurement and data fitting results of the time-varying characteristics of the resin modulus in Example 2 of the present invention;

[0035] Figure 3Schematic diagram of the process of characterizing the time-varying characteristics of mechanical properties during the curing process of composite materials. DETAILED DESCRIPTION

[0036] The present application is further described in detail below with reference to the accompanying drawings.

[0037] Example 1

[0038] like Figure 3 As shown, the present invention provides a method for characterizing the time-varying characteristics of mechanical properties during the curing process of a thermosetting resin-based composite material, comprising the following steps:

[0039] Step 1: Measurement of curing reaction enthalpy. Test and calculate the reaction enthalpy H released by the complete curing of the prepreg per unit mass according to ASTM E2160.

[0040] Step 2: Preparation of compression specimen in thickness direction. According to the symmetry [0 / 90] ns The prepregs are laid out in a ply order to form prepreg blanks. After sufficient cold drawing and compaction, the edges of the prepreg blanks are trimmed to prepare compression specimens.

[0041] Step 3: DSC (Differential Scanning Calorimeter) Sample Preparation: Take an appropriate amount of the prepreg to be tested and place it in an aluminum crucible to prepare a DSC sample. The DSC sample should contain 5 to 25 mg of prepreg sample.

[0042] Step 4: Preparation of samples with different curing degrees. According to the curing process parameters recommended by the prepreg supplier, the compression sample prepared in step 2 and the DSC sample prepared in step 3 are cured simultaneously using a composite material repair instrument, and the curing process is terminated at an appropriate time, and the temperature T at which the curing is terminated is recorded.

[0043] Step 5: Characterization of compression properties of prepregs with different curing degrees The compression modulus of the compression specimens prepared in step 4 at temperature T is measured using a mechanical testing machine.

[0044] Step 6: Characterization of the degree of curing: Perform a dynamic DSC scan on the DSC sample in step 4 to obtain the residual reaction enthalpy ΔH per unit mass of the sample, and calculate the degree of curing of the DSC sample in step 4 according to α=(1-ΔH) / H.

[0045] Step 7: Repeat steps 1 to 6 to obtain the compression modulus of the composite material in the thickness direction at different degrees of curing.

[0046] Step 8: Based on the compression modulus of the composite material in the thickness direction at different degrees of cure obtained in step 7, the modulus of the resin at different degrees of cure is inferred using the self-consistent field micromechanics model, and then the relationship between the engineering constants of the composite material and the degree of cure can be obtained.

[0047] Furthermore, in step 2, the recommended size of the compression specimen in the thickness direction is 50mm*50mm, and the ply information is [0 / 90] ns Here n should be no less than 5.

[0048] Furthermore, in step 5, the testing machine should be equipped with a temperature control box.

[0049] Furthermore, in step 5, the temperature control box of the testing machine should be set in advance and preheated to temperature T before step 4 ends.

[0050] Furthermore, in step 5, the sample should be compressed quickly after step 4, and safety precautions should be taken during the sample transfer process.

[0051] Furthermore, in step 5, the compressive elastic modulus should be calculated based on the force-displacement curve obtained from the compression test, taking the linear segment of the initial compression stage, and the calculation method is: Where F represents force, S represents the effective compression area, L0 represents the compression amount of the material, and L represents the original thickness of the specimen.

[0052] Furthermore, in step 7, the number of repetitions of steps 1 to 6 should not be less than 5 times.

[0053] Furthermore, in step 7, each time step 4 is repeated, a time different from that in the previous repeated test should be selected to terminate the curing process. It is recommended to reasonably select the curing process termination time based on the curing kinetics of the prepreg being tested, with equal curing degree interval as the goal.

[0054] Furthermore, in step 7, the number of samples with different curing degrees after the prepreg system reaches the gel point should be no less than 3.

[0055] Example 2

[0056] The present invention provides a method for characterizing the time-varying characteristics of mechanical properties of a thermosetting resin-based composite material during the curing process, comprising the following steps:

[0057] Step 1: Measurement of curing reaction enthalpy. Taking T800 grade carbon fiber unidirectional prepreg as the object, the dynamic DSC scanning curve of the prepreg system is measured according to the ASTM E2160 test method, as shown in Figure 1 The exothermic peak is integrated to obtain the reaction enthalpy H released by complete curing per unit sample mass = 114.38 J / g.

[0058] Step 2: Preparation of compression specimen in thickness direction. According to the symmetry [0 / 90] 10s The prepregs are laid out in a ply order to form prepreg blanks. After sufficient cold drawing and compaction, the edges of the prepreg blanks are trimmed to prepare compression specimens.

[0059] Step 3: DSC sample preparation: Take an appropriate amount of the prepreg to be tested and place it in an aluminum crucible to prepare a DSC sample.

[0060] Step 4: Preparation of samples with different curing degrees. According to the curing process parameters recommended by the prepreg supplier, the compression sample prepared in step 2 and the DSC sample prepared in step 3 are cured simultaneously using a composite material repair instrument, and the curing process is terminated at an appropriate time, and the temperature T at which the curing is terminated is recorded.

[0061] Step 5: Characterization of compression properties of prepregs with different curing degrees The compression modulus of the compression specimens prepared in step 4 at temperature T is measured using a mechanical testing machine.

[0062] Step 6: Characterization of the degree of curing: Perform a dynamic DSC scan on the DSC sample in step 4 to obtain the residual reaction enthalpy ΔH per unit mass of the sample, and calculate the degree of curing of the DSC sample in step 4 according to α=(1-ΔH) / H.

[0063] Step 7: Repeat steps 1 to 6 for 9 times to obtain the compression modulus of the composite material in the thickness direction at 9 different degrees of curing.

[0064] It is understandable that when there are sufficient curing equipment, curing processes with different stop times can be performed simultaneously.

[0065] Step 8: Based on the compression modulus of the composite material in the thickness direction at different curing degrees obtained in step 7, the modulus of the resin at different curing degrees is inferred using the self-consistent field micromechanics model. The expression of the self-consistent field micromechanics model is:

[0066]

[0067]

[0068] In the above formula,

[0069]

[0070] E is the elastic modulus, G is the shear modulus, and ν is the Poisson's ratio; subscripts 1, 2, and 3 represent directions, where 1 is the fiber direction, 2 is the direction perpendicular to the fiber in the plane, and 3 is the direction perpendicular to the fiber out of the plane; subscripts r and f represent resin and fiber; V f is the fiber volume fraction; k r and k f Divided into bulk modulus of resin and fiber.

[0071] Substituting the mechanical parameters of carbon fiber (Table 1), fiber volume fraction 0.56 and compression modulus data of samples with different curing degrees in the thickness direction into the self-consistent field micromechanics model, the elastic modulus of the resin at different curing degrees can be obtained, as shown in Table 2.

[0072] Table 1 Carbon fiber mechanical properties parameters of the measured prepreg system

[0073] parameter Value GPa parameter Numeric parameter Numerical Gpa e1f 250 v12f 0.2 g12f 15 e2f 25 v13f 0.2 g13f 12 e3f 25 v23f 0.35 g23f 5

[0074] Table 2 Thickness compression modulus of the prepreg system measured at different degrees of curing and its inverse resin modulus

[0075] Compression modulus / MPa 34.2 61.5 111.9 121.4 125.6 153.2 334 2904 8000 Sample curing degree 0 0.0015 0.0068 0.048 0.087 0.24 0.56 0.66 1 Reverse resin modulus / Mpa 8.5 15 25 30 31 39 85 850 3000

[0076] From the inverse resin modulus data, we can see that the modulus of the resin before the gel point (corresponding to a degree of curing of about 0.53) is small and does not change much, so the CHILE (α) model is selected for fitting, as shown in Figure 2 As shown, the curing degree and resin modulus E r The change relationship is:

[0077]

[0078] By substituting the fitting results of the CHILE (α) model into the self-consistent field micromechanics model, the mechanical properties of the composite material at any degree of curing can be obtained.

[0079] Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which are within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for characterizing the time-varying characteristics of mechanical properties during the curing process of a composite material, characterized in that: include: Step 1: Obtain the reaction enthalpy released by the complete curing of the prepreg to be tested per unit mass; Step 2: Obtain multiple sets of compression specimens and DSC specimens; Step 3: Use a composite material repair instrument to cure the compression specimen and the DSC specimen at the same time, terminate the curing process for each group of specimens at a different preset time, and record the temperature T of each group of specimens at the end of curing; Step 4: For each group of samples, use a mechanical testing machine to measure the compression modulus of the compressed sample after step 3 at the corresponding temperature T to obtain the degree of curing of the DSC sample after step 3; Step 5: Based on multiple groups of curing degrees and compression moduli, the self-consistent field micromechanics model is used to inversely infer the modulus of the resin at different curing degrees, and then the time-varying characteristics of the mechanical properties of the composite material during the curing process can be obtained.

2. The method for characterizing the time-varying characteristics of mechanical properties of composite material during curing process according to claim 1, characterized in that: Obtain the reaction enthalpy H released by the complete curing of the prepreg to be tested per unit mass, including: The reaction enthalpy H released by the complete curing of the prepreg per unit mass is tested and calculated according to ASTM E2160.

3. The method for characterizing the time-varying characteristics of mechanical properties of composite material during curing process according to claim 2, characterized in that: Obtaining the degree of curing of the DSC sample after step 3, including: The DSC sample is subjected to dynamic DSC scanning to obtain the residual reaction enthalpy ΔH per unit mass of the sample, and the curing degree α of the DSC sample is calculated according to α=(1-ΔH) / H.

4. The method for characterizing the time-varying characteristics of mechanical properties of composite materials during curing process according to claim 1, characterized in that: Obtain compression specimens, including: According to symmetry [0 / 90] ns The prepreg is laid in a ply order to form a prepreg blank, and after sufficient cold drawing and compaction, the edge of the prepreg blank is trimmed to obtain a compression specimen; The size of the compression specimen is 50mm*50mm, and the ply information is [0 / 90] ns Where n is a positive integer not less than 5.

5. The method for characterizing the time-varying characteristics of mechanical properties of composite materials during curing process according to claim 1, characterized in that: Obtain DSC samples, including: 5 to 25 mg of the prepreg to be tested was placed in an aluminum crucible to prepare a DSC sample.

6. The method for characterizing the time-varying characteristics of mechanical properties of composite materials during curing process according to claim 1, characterized in that: The mechanical testing machine is equipped with a temperature control box. When the compression modulus is measured using the mechanical testing machine, the temperature of the temperature control box is controlled to be T.

7. The method for characterizing the time-varying characteristics of mechanical properties of composite materials during curing process according to claim 1, characterized in that: The compression modulus of the compressed sample after step 3 at the corresponding temperature T is measured using a mechanical testing machine, including: A compression test is performed on the compression specimen to obtain a force-displacement curve, and a set of force F and compression displacement l0 is obtained from the linear segment of the initial compression stage in the force-displacement curve; According to the force F and the compression displacement l0; using the formula Obtain the compression modulus E; Among them, S represents the effective compression area and l represents the original thickness of the sample.

8. The method for characterizing the time-varying characteristics of mechanical properties of composite materials during curing process according to claim 1, characterized in that: Obtain multiple sets of compression and DSC specimens, including: Obtain no less than 5 sets of compression specimens and DSC specimens.

9. The method for characterizing the time-varying characteristics of mechanical properties of composite materials during curing process according to claim 1, characterized in that: After obtaining the degree of curing of the DSC sample after step 3, the method further comprises: Determine whether the number of samples with a degree of cure exceeding a preset gel point is less than 3; If yes, add a new sample group and a different preset time.

10. A device for characterizing the time-varying characteristics of mechanical properties during the curing process of a composite material, characterized in that: Used to perform the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A method for predicting the curing deformation of resin-based composite materials

    CN110197008B

  • Interactive coupling numerical simulation method for molding temperature field of composite autoclave

    CN107025366A

  • Prediction method for curing reaction of resin-based composite material

    CN110197009A

  • COMSOL-based curing multi-field coupling simulation modeling method for composite materials with different layering parameters

    CN119170169A

  • System and method for monitoring and controlling production of composite materials

    US20160339649A1